Inhibition of c-Jun N-terminal kinase signaling promotes osteoblastic differentiation of periodontal ligament stem cells and induces regeneration of periodontal tissues. (February 2022) - Kaneko, Hiroshi; Hasegawa, Daigaku; Itoyama, Tomohiro; Yoshida, Shinichiro; Tomokiyo, Atsushi; Hamano, Sayuri; Sugii, Hideki; Maeda, Hidefumi
Abstract: Objectives: Few clinical treatments to regenerate periodontal tissue lost due to severe endodontic and periodontal disease have yet been developed. Therefore, the development of new treatment methods for the regeneration of periodontal tissue is expected. The purpose of this study was to investigate the effects of a c-Jun N-terminal kinase (JNK) inhibitor, SP600125, on the osteoblastic differentiation of periodontal ligament stem cells (PDLSCs) in vitro, and the function of SP600125 on the regeneration of alveolar bone in vivo. Design: Alizarin red S staining, quantitative RT-PCR, and western blotting analysis was performed to determine whether SP600125 affects osteoblastic differentiation of human PDLSCs (HPDLSCs) and bone-related intracellular signaling. The effect of SP600125 on the regeneration of alveolar bone was assessed by using a rat periodontal defect model. The healing of periodontal defects was evaluated using micro-CT scans and histological analysis. Results: SP600125 promoted the osteoblastic differentiation such as Alizarin red S-positive mineralized nodule formation and the expression of osteoblast-related genes in HPDLSCs under osteogenic conditions. In addition, this inhibitor upregulated the BMP2 expression and the phosphorylation of Smad1/5/8 in HPDLSCs under the same conditions. The inhibition of Smad1/5/8 signaling by LDN193189 suppressed the SP600125-induced osteoblastic differentiation of HPDLSCs. Furthermore, the application of SP600125 promoted the regeneration of not only alveolar bone but also PDL tissue in periodontal defects. Conclusion: This study suggested that inhibition of JNK signaling promotes the osteoblastic differentiation of HPDLSCs through BMP2-Smad1/5/8 signaling, leading to the regeneration of periodontal tissues such as alveolar bone and PDL tissue. Highlights: A JNK inhibitor, SP600125, promotes osteoblastic differentiation of PDL stem cells. Smad1/5/8 mediates SP600125-induced osteoblast differentiation of PDL stem cells. SP600125 promotes periodontal tissue regeneration at periodontal defects.